Challenges of physiotherapy during humanized labor: integrative review (Research, Society and Development, 2022)
This integrative review aimed to describe the process of humanized childbirth and the challenges of physical therapy during this process, through searches were performed in the bases BVS, Scielo, PubMed, and Google Academic and PEDro using combinations of descriptors. There were after applying the eligibility criteria 6 publications in this review from the period 2017 to 2022. It was found that the challenges of physiotherapy in the process of humanized childbirth are many, from the implementation in practice of the policy of humanization of hospital care, from the direct influence of the institutional mission in the continuation of the technicist modus operandi of childbirth, from the training, training, recognition, hiring and sensitivity of physiotherapy professionals in this performance. However, it is recommended that further research be conducted to strengthen this role and reduce the challenges presented in this review.